Determinants of Halal Skincare Preferences: Do Digital Literacy and Religiosity Matter? - Annisa Wahdania; Intan Kusuma Pratiwi; Nuraeda (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2026)
This study aims to determine and analyze the influence of attitude and perceived behavioral control on halal skincare purchase preferences, with digital halal literacy and religiosity as moderating variables among Muslim Generation Z consumers in Mataram City. This research employed a quantitative approach with an associative research design. The sampling technique used was non-probability sampling with a purposive sampling method. The sample consisted of 443 Muslim Generation Z consumers in Mataram City. Data were collected through questionnaires using a Likert scale and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The results showed that the attitude variable had a T-statistics value of 2.661 and a P-values value of 0.004, indicating a positive and significant effect on halal skincare purchase preferences. The perceived behavioral control variable had a T-statistics value of 2.816 and a P-values value of 0.002, also indicating a positive and significant effect on halal skincare purchase preferences. Furthermore, the digital halal literacy variable had a T-statistics value of 3.293 and a P-values value of 0.000, while the religiosity variable had a T-statistics value of 2.280 and a P-values value of 0.011, both showing positive and significant effects on halal skincare purchase preferences. In addition, digital halal literacy and religiosity were found to moderate the influence of attitude and perceived behavioral control on halal skincare purchase preferences.